Radiation-induced brain injury: A review - Robbins, Michael; Greene-Schloesser, Dana; Peiffer, Ann M.; Shaw, Edward; Chan, Michael D.; Wheeler, Kenneth T. (Frontiers in Oncology, 2012)
Approximately 100,000 primary and metastatic brain tumor patients/year in the US survive long enough (> 6 months) to experience radiation-induced brain injury. Prior to 1970, the human brain was thought to be highly radioresistant; the acute CNS syndrome occurs after single doses > 30 Gy; white matter necrosis occurs at fractionated doses > 60 Gy. Although white matter necrosis is uncommon with modern techniques, functional deficits, including progressive impairments in memory, attention, and executive function have become important, because they have profound effects on quality of life. Preclinical studies have provided valuable insights into the pathogenesis of radiation-induced cognitive impairment. Given its central role in memory and neurogenesis, the majority of these studies have focused on the hippocampus. Irradiating pediatric and young adult rodent brains leads to several hippocampal changes including neuroinflammation and a marked reduction in neurogenesis. These data have been interpreted to suggest that shielding the hippocampus will prevent clinical radiation-induced cognitive impairment. However, this interpretation may be overly simplistic. Studies using older rodents, that more closely match the adult human brain tumor population, indicate that, unlike pediatric and young adult rats, older rats fail to show a radiation-induced decrease in neurogenesis or a loss of mature neurons. Nevertheless, older rats still exhibit cognitive impairment. This occurs in the absence of demyelination and/or white matter necrosis similar to what is observed clinically, suggesting that more subtle molecular, cellular and/or microanatomic modifications are involved in this radiation-induced brain injury. Given that radiation-induced cognitive impairment likely reflects damage to both hippocampal- and non-hippocampal-dependent domains, there is a critical need to investigate the microanatomic and functional effects of radiation in various brain regions as we